When Political Promises Become a Fiscal Burden: An Analysis of the Implementation of Indonesia's Free Nutritious Meals Program - Rahmat Kausar (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
Indonesia's Free Nutritious Meals (Makan Bergizi Gratis, MBG) program represents the transformation of an electoral promise into a large, nationwide recurrent spending commitment. Although international evidence supports school feeding as an instrument of social protection, education, and human capital development, its effectiveness depends on fiscal capacity, accurate targeting, nutritional quality, food safety, procurement integrity, and monitoring. This study analyzes MBG implementation through a rapid systematic literature review of scholarly publications, official documents, and credible policy data published between 2011 and June 2026. The review synthesizes evidence across four dimensions: substantive benefits, fiscal risks, implementation capacity, and public accountability. The findings indicate that school feeding can improve attendance, household food security, selected nutritional outcomes, and local food-system linkages when program design and delivery are adequate. However, the rapid expansion of MBG into a major national expenditure item creates risks of budget rigidity, weak targeting, supplier concentration, uneven kitchen standards, food-safety incidents, and broader macro-fiscal pressure. The analysis also shows that measuring success only by meals distributed is insufficient because program performance should be assessed through nutritional, educational, safety, fiscal, and local-economic outcomes. The study concludes that MBG requires phased expansion, vulnerability-based prioritization, transparent and decentralized procurement, real-time food-safety monitoring, outcome-based evaluation, and explicit fiscal safeguards. Without these reforms, a nutrition intervention intended to strengthen human capital may become politically popular while imposing growing administrative and fiscal burdens